The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/polym13162641
|View full text |Cite
|
Sign up to set email alerts
|

Binary Graft of Poly(N-vinylcaprolactam) and Poly(acrylic acid) onto Chitosan Hydrogels Using Ionizing Radiation for the Retention and Controlled Release of Therapeutic Compounds

Abstract: In this study, we carried out the synthesis of a thermo- and pH-sensitive binary graft, based on N-vinylcaprolactam (NVCL) and pH sensitive acrylic acid (AAc) monomers, onto chitosan gels (net-CS) by ionizing radiation. Pre-oxidative irradiation and direct methods were examined, and materials obtained were characterized by FTIR-ATR, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and swelling tests (equilibrium swelling time, critical pH, and temperature). The best synthesis radiation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In addition, micrographs confirmed that the CNCs were not grafted on the AAm polymeric chains since the reinforced hydrogels showed as smooth a porous structure as the control sample (0% CNC), while grafted networks usually look rougher with thin fibers joining the polymeric chains [ 38 , 46 ]. Therefore, the CNC was fully integrated into the AAm network when gamma radiation was used to synthesize the hydrogels, thus confirming that it did not interfere with the polymerization and crosslinking processes of AAm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, micrographs confirmed that the CNCs were not grafted on the AAm polymeric chains since the reinforced hydrogels showed as smooth a porous structure as the control sample (0% CNC), while grafted networks usually look rougher with thin fibers joining the polymeric chains [ 38 , 46 ]. Therefore, the CNC was fully integrated into the AAm network when gamma radiation was used to synthesize the hydrogels, thus confirming that it did not interfere with the polymerization and crosslinking processes of AAm.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristic of hydrogels is their ability to retain a large amount of water or aqueous solutions [ 46 , 47 ], so it is important to characterize this property. Figure 7 shows the swelling of hydrogels at different doses and CNC concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homopolymer was removed with the water-methanol mixture to evaluate the efficiency of the graft copolymerization. Although there are no unified definitions for calculating the parameters of the graft copolymerization, herein we report the use of the grafting yield (G) and the copolymerization yield (Y) (Equations ( 1) and ( 2)) [41]:…”
Section: Synthesis Of the Adsorbent Materialsmentioning
confidence: 99%
“…This polysaccharide is quite thermally stable and is structured of linear chains, but can be easily crosslinked [ 9 ], so it is possible to obtain higher molecular weight polymers to form films or hydrogel networks [ 10 ]. The use of chitosan is convenient for sanitary dressing, nanoparticle loading [ 11 ], and drug loading/delivery systems [ 7 , 12 ] due to its high hydrophilicity. Traditionally, the crosslinking of chitosan hass been carried out in acetic acid [ 13 , 14 ], with different crosslinking agents [ 15 , 16 , 17 ], and even using ionic liquids as solvent [ 18 ].…”
Section: Introductionmentioning
confidence: 99%